Prevalence and outcome of cardiac amyloidosis in an all-comer population of patients with non-ischaemic heart failure. (14th October 2021) - Goebel, S; Schwuchow-Thonke, S; Hahad, O; Brandt, M; Von Henning, U; Escher, F; Karbach, S; Braun, A.S; Gori, T; Schultheiss, H.P; Muenzel, T; Wenzel, P
Abstract: Background: Cardiac amyloidosis (CA) is increasingly recognized as an underlying cause of heart failure with preserved ejection fraction (HFpEF), associated with high morbidity and mortality. However, most studies, solely investigated the prevalence of CA in special subgroups including HFpEF and severe aortic valve disease. Purpose: With the present study we sought to investigate prevalence of different phenotypes of CA in an all comer-population of patients with non-ischaemic heart failure (HF) and to analyze the impact of CA on all-cause mortality. Methods: The My Biopsy HF-Study (German clinical trials register number: 22178) is a retrospective monocentric study investigating the underlying etiology of HF in an all-comer population of patients with HF of unknown etiology. Patients presenting with symptoms of HF at the University Medical Centre between 14/10/2012 and 01/03/2021, who underwent endomyocardial biopsy (EMB) were enrolled in the present study. Ischaemic HF and valvular HF were ruled out prior to EMB. Specimens were sent for further examination to a specialized laboratory approved by the Food and Drug Administration Results: Between October 2012 and March 2021, 767 patients (71.6% men) with HF of unknown etiology were included. Mean age at the time of presentation was 55.4 years (±14.4). Altogether, 72.5% of the patients presented with HF with reduced ejection fraction (HFrEF), 7.1% were diagnosed with HF with mid-range ejection fraction (HFmrEF) and 20.4% with HFpEF. Based on histological examination and genotyping, CA was diagnosed in 44 (5.7%) patients (immunglobulin light chain [AL] CA: 15 patients; variant transthyretin [ATTRv] CA: 6 patients; wild type transthyretin [ATTRwt] CA: 21 patients; de novo CA: 2 patients). Patients with CA were older compared with patients without CA (69.4±11.4 vs. 54.1±14.5; p<0.0001), had a higher prevalence of arterial hypertension (68.2% vs. 50.9%; p=0.045) and showed a better left ventricular ejection fraction based on echocardiographic examination (47.5% vs. 32.6%; p<0.0001). With respect to biomarker expression, levels of both brain natriuretic peptide and high-sensitive troponin I were significantly higher in patients without CA (BNP: 914.1 vs 612; p=0.01; troponin I: 812.8 vs. 171.7; p=0.006). In univariate logistic regression analysis CA was associated with a significant all-cause mortality (hazard ratio [HR] per unit increase [ui], 5.17, 95% CI, 2.93–9.08; p<0.0001), even after adjustment for classical cardiovascular risk factors (HRperui 3.12, 95% CI, 1.11–8.76; p=0.03) and comorbidities like chronic obstructive pulmonary disease, chronic kidney disease and stroke (HRperui 2.93, 95% CI, 1.2–7.15; p=0.018). Conclusions: Among patients presenting with HF of unknown etiology, including patients with HFpEF, HFmrEF and HFrEF, cardiac amyloidosis is the underlying cause of HF in 5.7% of patients and is independently associated with all-cause mortality. Funding Acknowledgement: Type of funding sources: None.